DISTRIBUSI KARBONDIOKSIDA (CO2) TANAH PADA KAWASAN KARST GUNUNGSEWU (Kasus Profil Tanah Daerah Sekitar Mata Air Ngeleng, Giritirto, Purwosari, Gunungkidul) - , DANARDONO; , Dr. Eko Haryono, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Carbondioxide is a one of major constituence for dissolution process in carbonate rock which can be taken from atmosphere or soil underground. Carbondioxide gaseous in atmosphere which likely to be less varied than soil carbondioxide causing variation of carbonate rock dissolution is more influenced on the content and distribution of soil carbondioxide, especially during summer season. This research is taken place in Karst Gunungsewu region exactly on soil profiles around Ngeleng Spring, Giritirto, Gunungkidul. The purpose of this research is (1) To assess and identified the value of vertical and temporally carbondioxide variation in soil profiles on forest land and dry land